The use of models to influence the grazing sites chosen by Barnacle Geese on Islay, Scotland - Zhu, Xian; Houston, David C; Percival, Stephen (Wildfowl, 1987)
Models of Barnacle Geese Branta leucopsis were used to determine whether they could manipulate the grazing impact of the geese. Models in a feeding posture were clearly more attractive than those in alert postures. However, feeding geese tended to move away from models and to spend less time in sectors with models than in empty sectors. In a situation where there is limited grazing there would be little overall effect of using models.